ANALISIS LAPORAN KEUANGAN DENGAN METODE TIME SERIES PADA PERUSAHAAN FOOTWEAR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Antonio, Ryan; Jusuf, A An Arief (Seminar Nasional Ilmu Terapan, 2024)
Financial statement analysis using the time series method is a process used to analyze and evaluate the financial condition of a company from one period to another. The Time series method itself involves financial ratios by comparing the financial ratios of companies in the same sector from year to year. This allows companies to see company’s financial trends over time and identify certain changes. In this case, financial statement analysis will be used to assess the finances of footwear sector companies listed on the Indonesia Stock Exhange (IDX) for the period 2018-2022. The results of the research conclusions are based on calculation of the profitabililty ratio, the footwear sector companies that has good financial performance seen from gross profit margin is PT Sepatu Bata Tbk (BATA) but from net profit margin, return on asset, return on equity is PT Primarindo Asia Infrastructures Tbk (BIMA). In the liquidity ratio that has a good financial performance seen from the cash ratio is PT Sepatu Bata Tbk (BATA) but from current ratio dan quick ratio is PT Primarindo Asia Infrastructures Tbk (BIMA). In the solvency ratio that has good financial performance seen and assessed debt to equity ratio and debt to asset ratio is PT Sepatu Bata Tbk (BATA). In the activity ratio that has good financial performance seen from inventory turnover is PT Primarindo Asia Infrastructures Tbk (BIMA) but for receivable turnover, working capital turnover, fixed asset turnover, total asset turnover is PT Sepatu Bata Tbk (BATA).